COVID-19 syndemics and the Global South
1 online resource.
Keywords: "This book focuses on syndemics in the Global South and uses COVID-19 as a window to understand clusters of disparities and disease comorbidities. The pandemic has exposing and multiplied structural inequalities and certain subpopulations were more exposed to COVID-19 as well as experienced greater morbidity and mortality. The effects of the pandemic differ between countries but have had an especially major impact, although in varying ways, in the Global South. The contributions in this volume explore the differential impacts of COVID-19 at individual, community, national, or regional levels, considering how structural violence is institutionalized in a way that creates vulnerable situations and disproportionate suffering. The book will be of interest to anthropologists and sociologists as well as those working in global and public health"--